A viewpoint on folklore education: providing students freedom and empowerment - Agung, Antonius Setyawan Sugeng Nur; Suryaman, Maman; Sayuti, Suminto A. (Journal of Education and Learning (EduLearn), 2024)
Oral folklore tradition is a unique phenomenon in West Borneo. This study aims to gain the lecturer's perspectives and reflection toward its implementation as a project-based activity for encouraging university students to transform local folklore into texts in English. It combines Finnegan's instructional procedure, and Gordon's synectic model and the creative state, which has been defined as creative instruction. Multiple observations and an in-depth interview with the folklore lecturer were conducted for this qualitative investigation. The lecturer is recognized as being exceptionally representative of this study employing purposive sampling under lived experience study because of his proficiency and enthusiasm. Having this creative instruction under supervision makes it clear that there is more room for the student's imagination and creativity to grow throughout this project-based activity. It gives them freedom to freely pursue their interests. Without excluding the possibilities of use in areas where there is still local folklore, this creative instruction is specifically suited for regions that are still rich in oral tradition. Further research is essential, nevertheless, as this study does not go into great detail on the perspectives and involvement among various students, the diversity of cultures and geographies, or the advancement of artificial intelligence (AI).